Understanding GPS/GNSS : principles and applications - Kaplan, Elliott D.; Hegarty, C. (Artech House, 2017)
Providing a comprehensive treatment of the Global Navigation Satellite System (GNSS), this reference offers both a quick overview of GNSS essentials and an in-depth treatment of advanced topics exploring all the latest advances in technology, applications, and systems. -- Edited summary from book.
Keywords: Global Positioning System.; elektronické knihy; electronic books